1997
DOI: 10.1111/j.1442-200x.1997.tb03584.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sponging and antipyretic medication to reduce body temperature in febrile children

Abstract: TWO hundred and twenty-four children aged 6 months to 5 years, with rectal temperatures greater than or equal to 39°C (104°F). were randomly treated with sponging alone or with medication including a single oral dose of aspirin 15 mgkg, or paracetamol 15 m a g , or ibuprofen 8 m a g . Twenty-three children were excluded from the final analysis because they did not complete the study. Demographic characteristics of the patients were found to be comparable in all groups. Rectal temperatures were recorded every 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 11 publications
3
43
0
3
Order By: Relevance
“…18 In some studies, the effects of paracetamol or ibuprofen became superior to sponging after 60 minutes. 8,11 In our study, we also observed lower axillary temperatures with dipyrone alone after this length of time, and there was also an increase in axillary temperature after 120 minutes. This can be explained as a rebound reaction because, unlike antipyretics, external cooling acts not by reducing the elevated set point but by overwhelming the metabolically expensive effector mechanisms that have been evoked by the elevated set-point.…”
Section: Referencessupporting
confidence: 72%
See 2 more Smart Citations
“…18 In some studies, the effects of paracetamol or ibuprofen became superior to sponging after 60 minutes. 8,11 In our study, we also observed lower axillary temperatures with dipyrone alone after this length of time, and there was also an increase in axillary temperature after 120 minutes. This can be explained as a rebound reaction because, unlike antipyretics, external cooling acts not by reducing the elevated set point but by overwhelming the metabolically expensive effector mechanisms that have been evoked by the elevated set-point.…”
Section: Referencessupporting
confidence: 72%
“…8,9,11 In a review, Bernath et al concluded that tepid sponging appears to be more effective within the first 30 minutes of treatment and has an additive effect when combined with paracetamol. 18 In some studies, the effects of paracetamol or ibuprofen became superior to sponging after 60 minutes.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1976 study showed that ibuprofen 6 mg/kg was as effective as APAP 12.5 mg/kg (15). APAP 15 mg/kg has been compared with ibuprofen 2.5 to 10 mg/kg in three studies (17)(18)(19). At this dose, APAP was superior to low doses of ibuprofen (2.5 to 5 mg/kg) but equivalent to higher doses (7.5 to 10 mg/kg).…”
Section: Efficacy Studiesmentioning
confidence: 99%
“…Six studies (Agbolosu, et al, 1997;Aksoylar et al, 1997;Brandts, 1997;Freidman & Barton, 1990;Kinmonth, 1992;& Steele, 1970;) examined the use of acetaminophen only as compared to sponging. All six reported acetaminophen alone reduced the fever more compared to sponging; however, only three studies (Agbolosu, et al, 1997;Freidman & Barton, 1990;Aksoylar et al, 1997) reported any statistical (p = <0.05) data.…”
Section: Acetaminophen Compared To Spongingmentioning
confidence: 99%